Penerapan model problem based learning untuk meningkatkan hasil belajar siswa kelas VI SD Negeri Rambeanak 2 tahun 2020/2021 - Edy Setyawibawa (Perkumpulan Kualitama Edukatika Indonesia, 2020)
The purpose of this study was to improve student learning outcomes through the Problem Based Learning learning model in grade VI SD Negeri Rambeanak 2. The type of research used was CAR. The research subjects of grade VI students. Data collection techniques using tests and observation results. The data analysis technique used is in the form of qualitative data and quantitative data. Pre-action learning outcomes of students who passed were only 9 students with a percentage of 37.5% then in cycle I increased to 16 students with a percentage of 66.7% and in cycle II increased to 20 students with a percentage of 83.3%. Thus, through the application of the Problem Based Learning learning model, it can improve the learning outcomes of class VI SDN Rambeanak 2 students.